Health Education and Diabetes Wound Care for the Elderly in Padang Pasir Village Community - Yannerith Chintya; M Ramadhani Firmansyah; Jenti Sitorus; Nonok Karlina; Nuraini (CV. Get Press Indonesia, 2025)
Diabetes mellitus (DM) is a chronic disease that has increased significantly in the last two decades, especially in the elderly population. This study aims to design and implement a comprehensive health education and diabetic wound care program for the elderly in urban communities. Methods. This study involved 30 elderly people who suffer from type 2 diabetes mellitus and live in the Padang Pasir Village area. The research instruments consisted of a knowledge questionnaire on diabetic wound care and a foot care skills observation sheet, which had been tested for validity and reliability in a previous study. Data was collected through questionnaires that were completed before and after the intervention. Results. The average overall knowledge score increased from 57.9 10.5 at the pre-test to 82.6 8.4 at the post-test, with a difference of +24.7 points. The knowledge aspect of foot wound prevention showed the highest increase, from 58.0 9.8 to 85.5 7.5, which reflects that after education, the elderly are more aware of the importance of preventive measures such as the use of appropriate footwear and regular foot examinations. Statistical analysis using paired t-test showed that the increase in knowledge and skills of the elderly after education was significant (p = 0.000). Conclusion. The educational intervention designed in this study was statistically and clinically effective, and can be recommended for wider implementation as part of a strategy to improve the quality of life of elderly people with diabetes.